The Third Wave: H7N9 Endemic Reassortant Viruses and Patient Clusters - Yisu Liu; Stéphane G Paquette; Li Zhang; Alberto J Leon; Weidong Liu; Wu Xiuming; Linxi Huang; Suwu Wu; Pengzhou Lin; Weihong Chen; Xibin Fang; Tiansheng Zeng; et al. (Journal of Infection in Developing Countries)
Southern China experienced few cases of H7N9 during the first wave of human infections in the spring of 2013. The second and now the third waves of H7N9 infections have been localized mostly in Southern China with the Guangdong province an epicenter for the generation of novel H7N9 reassortants. Clusters of human infections show human-to-human transmission to be a rare but well-documented event. A recent cluster of infections involving hospital health care workers stresses the importance of care givers utilizing personal protective equipment in treating H7N9 infected or suspected patients.